Eksistensi Public Relation Pemerintah Kota Yogyakarta Dalam Komunikasi Dan Negosiasi Kebijakan Relokasi Pedagang Kaki Lima - La Mani; Budi Guntoro; Mudiyono; Nunung Prajarto (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2016)
The local government as a system, organizationally, has the public relations (PR) board which should ideally have a large capacity in supporting the management of policy development. This study is intended to describe the existence of PR to support the successful implementation of relocation policies of street vendors in Yogyakarta City. This research is qualitative research with the unit of analysis is the staff of PR and information from the government of Yogyakarta City. The problem to be questioned is to what extent the local government PR is performing the function and roles based on the main duties and functions which is set based on, theoretically, the essence of the ideality. The results showed that the success of the relocation of street vendors in Yogyakarta City performed collaboratively between PR and its stakeholders. Processes and mechanisms impasses through the stages of fact-finding, planning, and negotiation. PR is not involved directly in the process of communication and negotiation with street vendors, but it has become a bridge of information, mediator, and facilitator in the process of relocation. Media of communication which widely used are mass media and interpersonal media. Both kinds of media are used by the PR board and its stakeholders in creating the awareness of the street vendors to be relocated.